In Vivo Positron Emission Tomography Imaging of Adenosine A2A Receptors - Sun, Meng-Juan; Liu, Fang; Zhao, Ya-Fei; Wu, Xiao-Ai (Frontiers in Pharmacology, 2020)
As an invasive nuclear medical imaging technology, positron emission tomography (PET) possess the possibility to imaging the distribution as well as the density of selective receptors via specific PET tracers. Inspired by PET, the development of radio-chemistry has greatly promoted the progress of innovative imaging PET tracers for adenosine receptors, in particular adenosine A2A receptors (A2ARs). PET imaging of A2A receptors play import roles in the research of adenosine related disorders. Several radio-tracers for A2A receptors imaging have been evaluated in human studies. This paper reviews the recent research progress of PET tracers for A2A receptors imaging, and their applications in the diagnosis and treatment of related disease, such as cardiovascular diseases, autoimmune diseases, neurodegenerative and psychiatric disease. The future development of A2A PET tracers were also discussed.